PENGARUH PENGETAHUAN, KEPERIBADIAN PROAKTIF DAN KEWASPADAAN BERWIRAUSAHA TERHADAP INTENSI BERWIRAUSAHA - Nisa, Salsa Khalifatun; Hiya Ratussalimah, Hiya Ratussalimah; Aiza Miftahul Aulia, Aiza Miftahul Aulia; Zarinda, Putri Mei Zarinda; Pratama, Yusa Hendra Pratama (Indonesian Educational Administration and Leadership Journal (IDEAL), 2021)
This study has a goal, namely to determine whether or not there is an influence between entrepreneurial knowledge, proactive personality and entrepreneurial vigilance on entrepreneurial intentions in Jambi University students. The sample used in this study was 272 students. Data collection using a questionnaire. The method of data analysis in this study uses quantitative methods supported by Smart PLS software version 3.2.9. The results of the study show that (1) entrepreneurial knowledge affects entrepreneurial vigilance. (2) Proactive personality influences entrepreneurial vigilance. (3) Entrepreneurial knowledge influences entrepreneurial intentions. (4) Proactive personality influences entrepreneurial intentions. (5) Entrepreneurial vigilance has no effect on entrepreneurial intentions. (6) Entrepreneurial knowledge influences entrepreneurial intentions through the intervening variable entrepreneurial vigilance. (7) Proactive personality has no effect on entrepreneurial intentions through the intervening variable entrepreneurial vigilance.Kata Kunci : Entrepreneurial intention, knowledge, proactive personality, vigilance